2010
DOI: 10.1088/1751-8113/43/31/315303
|View full text |Cite
|
Sign up to set email alerts
|

Smallest eigenvalue distribution of the fixed-trace Laguerre beta-ensemble

Abstract: In this paper we study entanglement of the reduced density matrix of a bipartite quantum system in a random pure state.It transpires that this involves the computation of the smallest eigenvalue distribution of the fixed trace Laguerre ensemble of N × N random matrices. We showed that for finite N the smallest eigenvalue distribution may be expressed in terms of Jack polynomials.Furthermore, based on the exact results, we found, a limiting distribution, when the smallest eigenvalue is suitably scaled with N fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 20 publications
1
56
0
Order By: Relevance
“…[7] for earlier heuristic arguments. Local statistics at the soft and hard edge have been analyzed for fixed trace β-ensembles in [37,14,30]. More general fixed trace models have been considered where the trace of a polynomial in the random matrix is fixed [5].…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…[7] for earlier heuristic arguments. Local statistics at the soft and hard edge have been analyzed for fixed trace β-ensembles in [37,14,30]. More general fixed trace models have been considered where the trace of a polynomial in the random matrix is fixed [5].…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…They allow to quantify the degree of entanglement of |ϕ by looking at the smallest (or largest) eigenvalue only. It distribution is known to be universal, agreeing with that of the Wishart-Laguerre ensemble without constraint [22]. In contrast, when the Hamiltonians are non-Hermitian, we keep the bases of left and right eigenvectors instead, as typically operators acting on |ϕ will yield complex eigenvalues.…”
Section: Introductionmentioning
confidence: 97%
“…In addition, for the regular Wishart-Laguerre ensemble we also indicate a relation between the recurrence relation and the determinantal results of Forrester and Hughes [28], and explicitly demonstrate the equivalence between the two results for rectangularity α = 0, 1. Similarly, for the fixed-trace scenario we prove the equivalence of the recursion-based expression and the result of Chen, Liu and Zhou [35] based on the inverse Laplace transform of a determinant, again for α = 0, 1.…”
Section: Introductionmentioning
confidence: 54%
“…The universality aspects of the regular Wishart-Laguerre ensemble have been explored in several notable works [29][30][31][32][33][34][38][39][40][41][55][56][57][58][59][60]. For the fixed trace case, the local statistical properties of the eigenvalues have been studied in [35,61]. In particular, it has been shown that the fixed trace and the regular Wishart-Laguerre ensembles share identical universal behaviour for large n at the hard edge, in the bulk and at the soft edge for α fixed [61].…”
Section: Large N α Evaluations and Comparison With Tracy-widom Densitymentioning
confidence: 99%
See 1 more Smart Citation